Intervention Services for Autistic Adults: An ASDEU Study of Autistic Adults, Carers, and Professionals' Experiences - Micai Martina; Ciaramella Antonio; Salvitti Tommaso; Fulceri Francesca; Fatta Laura Maria; Poustka Luise; Diehm Robert; Iskrov Georgi; Stefanov Rumen; Guillon Quentin; Rogé Bernadette; Staines Anthony; et al. (SPRINGER/PLENUM PUBLISHERS, 2022)
The Autism Spectrum Disorders in the European Union (ASDEU) survey investigated local services' use experiences of autistic adults, carers and professionals with interventions for autistic adults. The majority of the 697 participants experienced recommended considerations prior to deciding on intervention and during the intervention plan and implementation. Psychosocial interventions were the most commonly experienced interventions, while pharmacological interventions NOT recommended for core autistic symptoms were reported by fairly large proportions of participants. Family interventions were experienced slightly more commonly by carers than adults or professionals. Less than the 26% of autistic adult responders who had experienced challenging behaviors reported receiving an intervention to change them. These results provide insights for improving gaps in service provision of interventions among autistic adults.